1999
DOI: 10.1007/bf03033272
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate compartmentalization in the CNS

Abstract: Ascorbic acid, found physiologically as the ascorbate anion, is an abundant water-soluble antioxidant. It is concentrated in the intracellular compartment of all tissues in the body. The CNS has particularly high levels of ascorbate. Recent data from this laboratory indicate that ascorbate is distinctly compartmentalized between neurons and glia, with an average intracellular concentration of 10 mM in neurons and 1 mM in glial cells. These data can be contrasted with those for another important low molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…Postmortem findings showed a significant mean decrease of about 26% of ascorbic acid levels in caudate ϩ globus pallidus ϩ substantia nigra (68). As recalled above, ascorbic acid and GSH compartmentalization studies in the brain give an ascorbic acid-to-GSH ratio of 4:1 in neurons, with an opposite ratio of 1:4 in glia (62). Therefore, if GSH depletion is thought to occur in PD mainly in glia, that of ascorbic acid may most likely occur in neurons.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Postmortem findings showed a significant mean decrease of about 26% of ascorbic acid levels in caudate ϩ globus pallidus ϩ substantia nigra (68). As recalled above, ascorbic acid and GSH compartmentalization studies in the brain give an ascorbic acid-to-GSH ratio of 4:1 in neurons, with an opposite ratio of 1:4 in glia (62). Therefore, if GSH depletion is thought to occur in PD mainly in glia, that of ascorbic acid may most likely occur in neurons.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the ascorbate radical is quite unreactive and, unlike GS ⅐ , is not known to cause any biological damage (61). Ascorbic acid and GSH compartmentalization studies in the brain (62) show an ascorbic acid-to-GSH ratio of 4:1 in neurons (10 versus 2.5 mM, respectively), with an opposite ratio of 1:4 in glia (1 versus 4 mM, respectively). Sturgeon et al (59) demonstrated that in the presence of physiological concentrations of ascorbic acid and GSH, ascorbic acid, but not GSH, was involved in the detoxification pathway of oxidizing free radicals formed by peroxidase; therefore, ascorbic acid was considered the ultimate radical sink.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Vit C has been postulated to be a neuromodulator (Rice, 1999(Rice, , 2000 of both dopamine-and glutamate-mediated neurotransmission, and it is an essential co-factor for noradrenaline synthesis (see Coveñas et al, 2011a). The presence of Vit C in neurons of the locus coeruleus in all the cases studied in the present work is a clear morphological reflection of a neuromodulator role for this vitamin in the release of noradrenaline and acetylcholine from synaptic vesicles.…”
Section: Functional Interpretationmentioning
confidence: 99%
“…The presence of Vit C in neurons of the locus coeruleus in all the cases studied in the present work is a clear morphological reflection of a neuromodulator role for this vitamin in the release of noradrenaline and acetylcholine from synaptic vesicles. Since Vit C acts as a co-factor in the synthesis of many neuropeptides (Rice, 1999(Rice, , 2000, the detection of Vit C in neurons of brainstem regions such are the lateral reticular nucleus or the substantia nigra supports a role for this vitamin on the catecholaminergic function, although further studies are needed to establish the precise action of Vit C on these neurons.…”
Section: Functional Interpretationmentioning
confidence: 99%
“…The brain neither synthesizes vitamin C nor receives it across the BBB or arachnoid membrane (27). Neurons therefore depend upon a vitamin C supply mainly via the agency of the Na ascorbate cotransporter in CP epithelium (28). This cotransporter continually secretes ascorbate into CSF even in severe hypovitaminosis C. CPYCSF can thus constantly provide substantial amounts of vitamin C to neuronal networks.…”
Section: Subcortical Regions and Frontal Cortexmentioning
confidence: 99%